Empowering Elderly Hypertension through a Combination of Mindfulness Therapy and Emotional Freedom Technique (EFT) to Lower Anxiety - Khadijah, Siti; Ariani Sulistyowati, Dwi; Caturini Sulistiyowati, Endang (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2026)
The elderly population in Indonesia has a high prevalence of hypertension reaching 63.2%. This physical condition is exacerbated by anxiety reaching 45-60% in hypertensive elderly people in nursing homes who have not received comprehensive non-pharmacological interventions. This activity aims to empower the elderly in managing anxiety through the application of a combination of Mindfulness therapy and Emotional Freedom Technique (EFT). The program involves hypertensive elderly. The implementation method is carried out through the preparation stage, implementation; health education, demonstrations, hands-on practice of mindfulness and EFT therapy, mentoring, and evaluation of ability to practice therapy, and anxiety levels before and after the intervention using the Hamilton Anxiety Rating Scale (HARS) and structured questionnaires. This activity is supported by educational media in the form of pocket books and therapy guide videos. The results of the activity showed an increase in the knowledge and skills of the elderly in conducting therapy independently, a decrease in anxiety levels. The combination of mindfulness therapy and EFT has been shown to be effective in improving the ability of the elderly to manage anxiety and can be applied sustainably as a non-pharmacological approach to improve the quality of life of the elderly with hypertension.